2020
DOI: 10.3390/joitmc6030047
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Skills in Islamic Financial Innovation: Evidence from Bahrain and Malaysia

Abstract: A body of work has emerged that examines human capital from the perspective of skills to better understand the types of expertise that influence innovation. The relationship between skill and financial innovation, however, is poorly understood in the context of Islamic financial institutions (IFIs). IFIs are distinct from their conventional counterparts by their compliance with Shariah law. Based on a survey of IFIs in Bahrain and Malaysia, this paper examines the effect of different skills on IFI inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 55 publications
0
11
0
1
Order By: Relevance
“…Islamic finance shares some similarities in terms of market and credit risks with its traditional counterpart. However, it is different from non-Islamic finance by a second layer of Sharia risks [40]. Sinclair [41] indicated that legal institutions, which define not only incentives but also rights and obligations in financial contracts, are the core of financial innovations.…”
Section: Discussion: Performance Of Islamic Stock Portfolios and Open Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Islamic finance shares some similarities in terms of market and credit risks with its traditional counterpart. However, it is different from non-Islamic finance by a second layer of Sharia risks [40]. Sinclair [41] indicated that legal institutions, which define not only incentives but also rights and obligations in financial contracts, are the core of financial innovations.…”
Section: Discussion: Performance Of Islamic Stock Portfolios and Open Innovationmentioning
confidence: 99%
“…Sinclair [41] indicated that legal institutions, which define not only incentives but also rights and obligations in financial contracts, are the core of financial innovations. With many strong Islamic institutions, Malaysia has become the heart of financial innovations parallel with developing the regulatory environments to protect religious rules to minimise Islamic risks [40]. The application of the existing theories in open innovation to the Malaysian Islamic finance industry needs to be investigated cautiously, considering differences in regulatory and law aspects, capital markets, industry structure and cultural components.…”
Section: Discussion: Performance Of Islamic Stock Portfolios and Open Innovationmentioning
confidence: 99%
“…Adopting and practicing innovation is the key to post crisis growth and sustainability [90,94]. COVID-19 has paved way for the adoption of social and open innovation to thrive and grow [92,95].…”
Section: The Role Of Islamic Fintech In Open Innovation and Covid-19mentioning
confidence: 99%
“…It is no doubt that is an investment if a company has the high ethical standards as well as a liability as its ethical conduct [12]. Sustaining innovation through the ethical code of Shariah is the solution to establish and build a neighborhood company that provides optimal services [13].…”
Section: Discussionmentioning
confidence: 99%